PENGARUH TINGKAT PENDIDIKAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL DALTON MAKASSAR - Yusrab Ardianto Sabban (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This study aimed to obtain an explanatory findings were tested on the effect of (1) level of education and work discipline on the performance of employees, (2) level of education on employee performance, (3) work discipline on employee performance, and (4) level of education on the work discipline at Dalton Hotel Makassar. The research design used in this research is causal quantitative. The subjects of this research was all employees in Dalton Hotel and object of this research was level of education, work dicipline, and employee performance. The population of this research amount to 55 employees that are all used the unit of observation, so this research includes research population. The data was collected this research is the data level of education, work discipline, and employee performance which is based on employees and managers Dalton Hotel Makassar. The data were collected in this research a questionnaire and recording documents techniques then was analyzed using path analysis. The results of research showed there were a positive effect of (1) level of education and work discipline on the performance of employees, (2) level of education on employee performance, (3) work discipline on employee performance, and (4) level of education on the work discipline at Dalton Hotel Makassar.